2002
DOI: 10.1074/jbc.m201195200
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of New Cell Permeable C3-like Proteins That Inactivate Rho and Stimulate Neurite Outgrowth on Inhibitory Substrates

Abstract: The activation state of Rho is an important determinant of axon growth and regeneration in neurons. Axons can extend neurites on growth inhibitory substrates when Rho is inactivated by C3-ADP-ribosyltransferase (C3). We found by Rho-GTP pull-down assay that inhibitory substrates activate Rho. To inactivate Rho, scrapeloading of C3 was necessary because it does not freely enter cells. To overcome the poor permeability of C3, we made and characterized five new recombinant C3-like chimeric proteins designed to cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
87
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(90 citation statements)
references
References 39 publications
2
87
1
Order By: Relevance
“…Most studies have focused on two situations in which this occurs -neonatal spinal neurons, which often regenerate to produce complete functional recovery 91,92 , and regeneration of the results in regeneration 62 . It remains to be seen whether the effects of the new generation of C3 molecules, which are more membrane-permeable, can be similarly confined and effective 72 .…”
Section: Insight From Systems That Regenerate In Vivomentioning
confidence: 99%
“…Most studies have focused on two situations in which this occurs -neonatal spinal neurons, which often regenerate to produce complete functional recovery 91,92 , and regeneration of the results in regeneration 62 . It remains to be seen whether the effects of the new generation of C3 molecules, which are more membrane-permeable, can be similarly confined and effective 72 .…”
Section: Insight From Systems That Regenerate In Vivomentioning
confidence: 99%
“…The relative contribution of the neuroprotective effect of C3 and of long-distance axonal regeneration to functional recovery is unclear. Use of cell-permeable C3-like proteins (Winton et al, 2002) and a slow release protocol in vivo would help to define the contribution of these cellular responses.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that the Cterminal fusion of short transport peptide sequences enhances the cellular uptake of C3 (Sauzeau et al 2001;Park et al 2003;Winton et al 2002;Sahai and Olson 2006). In many studies, the C3 gene was introduced into eukaryotic target cells by transient and stable transfection using plasmids or by viral infection (Fujisawa et al 1998;Hill et al 1995;Caron and Hall 1998;Henning et al 1997;Meacci et al 1999;Genot et al 1996).…”
Section: C3 Toxins Are Pharmacological Toolsmentioning
confidence: 99%